The Wuhan cover-up : and the terrifying bioweapons arms race - Kennedy, Robert F., Jr., 1954- (Children's health defense., 2023)
Details how research to develop preemptive vaccines for animal viruses before they jump to humans--research that could also be used for the development of bioweapons--was outsourced to the Wuhan Institute of Virology and reveals the conspiracy to hide thesource and origin of the COVID-19 virus.